Design a Client-Side Application with Automatic Real-Time Phishing Detection Mechanism based on the White-Lists - Wadhwa, Sumit; Pratap Srivastava, Arun; Awasthi, Shashank; Kumar Singh, Mahesh (International Journal of Engineering and Technology, 2018)
Phishing is a problem involving not to be trusted emails and WebPages that trick unsuspecting users into willingly revealing their confidential information. Phishing is a cyber attack which involves a fake website mimicking the some real legitimate website. In this paper we design, implementation, and evaluation of phishing detection using HTML/CSS, PHP and store the credential details in session for the being time and can work with any authentication technologies which are based on exchange of credentials also discuss the detection of login phishing page that contains email and password, credential fields that provide personal/restricted content. Integrated security feature is one of the best  solution  for prevention a phishing attacks to secure web browser when-ever a phishing site is accessed by an internet user